China's One‐Child Policy: Some Unintended Consequences. (October 2014) - Howden, David; Zhou, Yang
Abstract This paper gives a brief overview of China's family planning policy which, although recently relaxed, still controls a large swath of the population. Unofficially known as the 'one‐child policy', it resulted from the social strife of the 1970s coupled with a Malthusian pessimism concerning the capability of the still largely closed and isolated Chinese economy to care for itself. We discuss the motivations for the policy, the unfortunate demographic future that it will create, and some policy reforms that can be undertaken today.